2016
DOI: 10.21746/ijbio.2016.04.0012
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of menstrual disorders with nutritional status of college girls from Bankura District, West Bengal, India.

Abstract: Menstrual disorders are the most common complaints of the women. This often leads to anxiety, depression and other such psychological problems. The present study was conducted to find out the association of nutritional status with menstrual pattern and menstrual disorders of college girls. This study was employed on ninety-seven female college students (18- 22 years) of Bankura district. A pre-tested, semi-structured questionnaire was used to collect socioeconomic data and information regarding menstrual patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Although high educational level was associated with premenstrual syndrome ( P value > 0.04), this association suggested that the higher level of education was probably associated with better information about healthy diet and lead to better comprehension of health status and menstrual symptom. Patsa et al found no association between PMS with socioeconomic status ( P value > 0.05) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although high educational level was associated with premenstrual syndrome ( P value > 0.04), this association suggested that the higher level of education was probably associated with better information about healthy diet and lead to better comprehension of health status and menstrual symptom. Patsa et al found no association between PMS with socioeconomic status ( P value > 0.05) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 In India, 54% of school children were under-nourished. 6 In Africa, the prevalence of iodine deficiency among school-age children was 39.3%. 7 In Ethiopia, the prevalence of wasting, underweight, and stunting among primary school children were 17.7%, 18.2%, and 21.3%, respectively.…”
Section: Introductionmentioning
confidence: 99%